2020
DOI: 10.5530/pj.2020.12.43
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile, Antioxidant Activity and Cell Line Study of Marine Red Macroalgae Eucheuma cottonii on Lung A-549 Cancer Cells

Abstract: Introduction: In this century, cancer has increased in incidence and become one of the deadliest disease in the world. However, to date, lung cancer treatments are still not fully effective, quite expensive and very exhaustive for the patient. Eucheuma cottonii is an abundant marine red macroalgae in Indonesia which have a potential anti-lung cancer properties. Aim of this research is to determine phytochemical profile of Eucheuma cottonii extracts, as well as to evaluate its antioxidant and cytotoxic effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Phytochemical analysis has been revealed that triterpenes are present in ample amount in that extract which could be attributed for these activities [26]. On the other hand, Indonesian seaweed Eucheuma cottonii contains triterpenoid which exhibited cytotoxicity against lung cancer cells at an IC 50 of 251.73 μg/mL [27]. Padina boergesenii has been reported to produce triterpenes that have antiangiogenic activity against renal carcinoma [28].…”
Section: Triterpenoidsmentioning
confidence: 99%
“…Phytochemical analysis has been revealed that triterpenes are present in ample amount in that extract which could be attributed for these activities [26]. On the other hand, Indonesian seaweed Eucheuma cottonii contains triterpenoid which exhibited cytotoxicity against lung cancer cells at an IC 50 of 251.73 μg/mL [27]. Padina boergesenii has been reported to produce triterpenes that have antiangiogenic activity against renal carcinoma [28].…”
Section: Triterpenoidsmentioning
confidence: 99%